2020
DOI: 10.1038/s41598-020-71593-8
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic oxygen carrier isolated from Arenicola marina decreased P. gingivalis induced inflammation and tissue destruction

Abstract: The control of inflammation and infection is crucial for periodontal wound healing and regeneration. M101, an oxygen carrier derived from Arenicola marina, was tested for its anti-inflammatory and anti-infectious potential based on its anti-oxidative and tissue oxygenation properties. In vitro, no cytotoxicity was observed in oral epithelial cells (EC) treated with M101. M101 (1 g/L) reduced significantly the gene expression of pro-inflammatory markers such as TNF-α, NF-κΒ and RANKL in P. gingivalis-LPS stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 90 publications
0
36
0
1
Order By: Relevance
“…Next to AMPs, other fields are investigated, and recently, an oxygen transporter derived from the marine lugworm Arenicola marina, HEMARINA-M101 (M101), was tested. M101's anti-inflammatory and anti-infectious potential, based on its anti-oxidative and tissue oxidation properties, have been tested in vitro on biofilm cultures containing Pg and in vivo in a Pg-induced subcutaneous calvarial abscess in a mouse model [271]. The results showed that M101 significantly reduced the release of pro-inflammatory cytokines and also had an anti-bacterial effect on Pg, confirming its pro-healing properties and making it a potential therapeutic agent in periodontal wound healing and regeneration [271].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…Next to AMPs, other fields are investigated, and recently, an oxygen transporter derived from the marine lugworm Arenicola marina, HEMARINA-M101 (M101), was tested. M101's anti-inflammatory and anti-infectious potential, based on its anti-oxidative and tissue oxidation properties, have been tested in vitro on biofilm cultures containing Pg and in vivo in a Pg-induced subcutaneous calvarial abscess in a mouse model [271]. The results showed that M101 significantly reduced the release of pro-inflammatory cytokines and also had an anti-bacterial effect on Pg, confirming its pro-healing properties and making it a potential therapeutic agent in periodontal wound healing and regeneration [271].…”
Section: Novel Therapeutic Strategiesmentioning
confidence: 99%
“…( [55][56][57][58] mice (70). Besides, the removal of ligatures allows the study of lesion healing and resolution of inflammation (53).…”
Section: Calvaria Inoculation Of Periodontitisassociated Bacteriamentioning
confidence: 99%
“… Proinflammatory cytokines regulate osteoclastogenesis via direct interaction with their receptors. Proinflammatory cytokines such as IL-1β, IL-6, IL-17, and TNF-α secreted by different immune cells induce RANKL production in endothelial cells ( Batool et al, 2020 ), fibroblasts ( Nagasawa et al, 2007 ; Hienz et al, 2015 ), and osteoblast lineage cells ( Algate et al, 2016 ). OPG, secreted by osteoblast, works as a decoy receptor of RANKL to negatively regulate osteoclastogenesis ( Lam et al, 2000 ).…”
Section: Physiological Osteoclastogenesismentioning
confidence: 99%
“…RANKL commits the cells to the osteoclastic lineage and TNF-α ensures the induction of differentiation through TNF-α receptor (TNFR) signaling, suggesting a synergistic relationship between RANKL and TNF-α ( Fuller et al, 2002 ). In contrast, LPS/TLR4 signaling initiates RANKL-dependent osteoclastogenesis partially by promoting RANKL production in osteoblasts ( Algate et al, 2016 ), gingival fibroblasts ( Nagasawa et al, 2007 ; Hienz et al, 2015 ), oral epithelial cells ( Batool et al, 2020 ), and DCs ( Alnaeeli et al, 2007 ). Inhibition of TLR4 and TLR2 in osteoblasts results in decreased RANKL expression even after exposure to LPS ( Tang et al, 2011 ).…”
Section: Osteoclastogenesis Under Pathological Conditionsmentioning
confidence: 99%